Transmission of chirality through space and across length scales - Morrow, S; Bissette, A; Fletcher, S (Nature Publishing Group, 2017)
Chirality is a fundamental property and vital to chemistry, biology, physics and materials science. The ability to use asymmetry to operate molecular-level machines or macroscopically functional devices, or to give novel properties to materials, may address key challenges at the heart of the physical sciences. However, how chirality at one length scale can be translated to asymmetry at a different scale is largely not well understood. In this Review, we discuss systems where chiral information is translated across length scales and through space. A variety of synthetic systems involve the transmission of chiral information between the molecular-, meso- and macroscales. We show how fundamental stereochemical principles may be used to design and understand nanoscale chiral phenomena and highlight important recent advances relevant to nanotechnology. The survey reveals that while the study of stereochemistry on the nanoscale is a rich and dynamic area, our understanding of how to control and harness it and dial-up specific properties is still in its infancy. The long-term goal of controlling nanoscale chirality promises to be an exciting journey, revealing insight into biological mechanisms and providing new technologies based on dynamic physical properties.